2015
DOI: 10.3390/rs70506336
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Radiometric Normalization of Road Points from Terrestrial Mobile Lidar System

Abstract: Lidar data provide both geometric and radiometric information. Radiometric information is influenced by sensor and target factors and should be calibrated to obtain consistent energy responses. The radiometric correction of airborne lidar system (ALS) converts the amplitude into a backscatter cross-section with physical meaning value by applying a model-driven approach. The radiometric correction of terrestrial mobile lidar system (MLS) is a challenging task because it does not completely follow the inverse sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Numerous studies [33,39,[45][46][47][48] revealed that the original backscattered intensity is inapplicable to discriminate the target surface properties directly. The radiometric correction is necessary to eliminate the impact of the distance and incidence angle on the intensity data and to convert the raw intensity into a corrected value that is proportional or equal to the target's reflectance [39,45,46,[49][50][51][52][53][54][55][56][57][58][59][60][61]. However, regarding the distance effect, due to the possible existence of automatic reducers for the near-distance backscattered signals and amplifiers for weak backscattered signals [46,62], only the part of the intensity data within a specific distance follows the theoretical LiDAR formula [39,48,61,63] and can be corrected effectively through 1/R 2 [33,34].…”
Section: Correction Of the Backscattered Intensitymentioning
confidence: 99%
“…Numerous studies [33,39,[45][46][47][48] revealed that the original backscattered intensity is inapplicable to discriminate the target surface properties directly. The radiometric correction is necessary to eliminate the impact of the distance and incidence angle on the intensity data and to convert the raw intensity into a corrected value that is proportional or equal to the target's reflectance [39,45,46,[49][50][51][52][53][54][55][56][57][58][59][60][61]. However, regarding the distance effect, due to the possible existence of automatic reducers for the near-distance backscattered signals and amplifiers for weak backscattered signals [46,62], only the part of the intensity data within a specific distance follows the theoretical LiDAR formula [39,48,61,63] and can be corrected effectively through 1/R 2 [33,34].…”
Section: Correction Of the Backscattered Intensitymentioning
confidence: 99%
“…The correction of incidence angle and distance effects based on reference targets is effective and feasible. The proposed method can also be applied to the radiometric correction of overlap scans [7,34]. The limitation of the proposed method is that its accuracy depends on the stability of systematic parameters, which can be a topic for future study.…”
Section: Discussionmentioning
confidence: 99%
“…The specific forms of f 2 (θ) and f 3 (d) are unknown and vary significantly in different scanners because manufactures always disclose the instrumental details [25]. Different empirical functions can be used to approximately substitute f 2 (θ) and f 3 (d) [18][19][20]22,23,25,26]. According to the conclusion in [25], based on the Weierstrass approximation theorem both f 2 (θ) and f 3 (d) can be empirically approximated by a polynomial regardless of the internal details of the instrumental mechanisms, i.e., f 3 , and β i are polynomial parameters.…”
Section: Principles Of Intensity Correctionmentioning
confidence: 99%